Thermodynamic and Micellar Studies on Iron and Cobalt Soap Solutions - RAWAT, M.K.; SINGH, NEETU (Asian Journal of Chemistry, 2010)
The investigations on the conductance of the solutions of iron and cobalt soaps in a mixture of benzene and methanol (50:50 v/v) have been made at different temperature to determine the critical micellization concentration, dissociation constant, molar conductance and thermodynamic parameters for dissociation and association process. The results show that the critical micellization concentration of these soaps increases with the increasing temperature. The values of enthalpy, free energy and entropy changes confirm the exothermic nature of dissociation process and decrease in free energy for association process shows that the micellization is favoured over dissociation process.